PM2.5-mediated photochemical reaction of typical toluene in real air matrix with identification of products by isotopic tracing and FT-ICR MS. (15th November 2022) - Li, Qianqian; Liu, Yalu; Wang, Mengjing; Su, Guijin; Wang, Qingliang; Zhao, Xu; Zhang, Qifan; Meng, Jing; Shi, Bin
Abstract: The sight into photoconversion of toluene, a ubiquitous typical pollutant, attentively by the involvement of PM2.5 in the real air environment is crucial for controlling haze pollution. Compared with the large-size PM2.5 on normal day (PM2.5-ND), the PM2.5 on haze day (PM2.5-HD) formed of small particle agglomerates featured greater oxidation capability, evidenced by the valence distribution of sulfur species. Notably, PM2.5-HD had abundant O2 − and OH and participated in the photochemical reaction of toluene, giving it a greater toluene conversion with a first-order kinetic rate constant of 0.4 d −1 on haze day than on normal day (0.2 d −1 ). During the toluene photoconversion, isotopic labelling traced small molecules including benzene and newfound pentane, ethylbenzene, 1, 3, 8-p-menthatriene and 4-methyl-1-pentanone benzene that could be formed by methyl breakage, ring opening, fragmentation reforming and addition reaction of toluene. Given ADMET properties, 1, 3, 8-p-menthatriene was assigned high priority since it had poor metabolism, low excretion and severe toxicity, while benzene and 4-methyl-1-pentanone benzene should also be noticeable. FT-ICR MS results indicated that toluene could create multiple macromolecular products that are more sensitive to SOA generation in haze air matrix with broader carbon number and O/C, more oxygenated substitution with CHO/CHON occupying by 81.4%, lower DBEaverage at 4.66 and higher O S C ‾ at −1.60 than normal air matrix. Accordingly, a photochemical reaction mechanism for toluene in real air atmosphere was proposed. The stronger oxidation property of PM2.5 not only facilitated toluene to generate small molecules but also boosted the conversion of intermediates to oxygenated macromolecular products, contributing to the formation of SOA. Graphical abstract: Image 1 Highlights: PM2.5 on haze day had higher oxidation capability with more O2 − . and OH. PM2.5- mediated reactive oxygen radical boosted photoconversion of toluene. Isotopic labelling traced four newfound products mostly with more toxicity. More macromolecular products were formed in haze air matrix by FT-ICR MS. They featured more oxygenated substitution, low DBEaverage, and higher O S C ‾ .